Job Protection, Minimum Wage and Unemployment - André Zylberberg; Pierre Cahuc (Institute for the Study of Labor (IZA), 1999)
We analyze how wage setting institutions and job-security provisions interact on unemployment. The assumption that wages are renegotiated by mutual agreement only is introduced in a matching model with endogenous job destruction – la Mortensen and Pissarides (1994) in order to get wage profiles with proper microfoundations. Then, it is shown that job protection policies influence the wage distribution and that government mandated severance transfers from employers to workers are not any more neutral, as in the standard matching model where wages are continuously renegotiated: In our framework high redundancy transfers influence employment. Moreover, the assumption of enegotiation by mutual agreement allows us to introduce a minimum wage in a coherent way, and to study its interactions with job protection policies. Our computational exercises suggest that redundancy transfers and administrative dismissal restrictions have negligeable unemployment effects when wages are flexible or when the minimum wage is low, but a dramatic positive impact on unemployment when there is a high minimum wage.
Keywords: J64; H29; J23; J38; J41; 330; Unemployment; job protection; minimum wage; matching models; renegotiation; Arbeitslosigkeit; Mindestlohn; Kündigungsschutz; Arbeitszeitflexibilisierung; Theorie